Risk perception by healthcare professionals related to drug use during pregnancy: a Swiss survey (Swiss Medical Weekly, 2014)
PRINCIPLE: Healthcare professionals’ (HCPs’) perception of risk associated with drug use in pregnancy may have an impact on the pharmacological treatment of some women. The aim of this study was to examine this risk perception in a sample of Swiss HCPs with a special focus on their knowledge and use of available specialised information sources. METHOD: An online, French and German, questionnaire was e-mailed to 7,136 members of four Swiss professional societies (gynaecologists, paediatricians, midwives and pharmacists). The questionnaire was designed (a) to collect demographic characteristics, (b) to evaluate the frequency of use of several specialised sources of information on drugs in pregnancy in their daily practice, and (c) to examine the perception of risk associated with drug use during pregnancy. RESULTS: A total of 1,310 questionnaires were collected (response rate of 18.4%). More than 80% of the respondent HCPs use the Swiss Drug Reference Book (Compendium) to assess the risk associated with drugs during pregnancy and are not aware of available specialised information sources (books, websites or information centres). Despite some disparities between HPCs, the risk related to drug intake was overall highly misperceived. Blinded reading of three product monographs in the Compendium was associated with an overestimated perception of risk (e.g., after reading the “paracetamol” monograph, 38% of the participants stated they would probably not advise the use of this drug to a pregnant patient). CONCLUSION: Overall, an overestimation of the risk associated with drug use during pregnancy has been observed in our sample of HCPs, which might be related to the underuse of specialised information source among other factors. These findings evidenced the need for increased training for HCPs in order to optimise medication use during pregnancy. Further studies are needed to confirm these results and identify causes.